2021
DOI: 10.1111/tan.14422
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of de novo donor‐specific HLA‐DPB1 antibodies in kidney transplantation

Abstract: HLA matching and avoidance of unacceptable mismatches are important aspects in the selection of donors for solid organ transplantation. The impact of HLA-DPB1 incompatibility on the outcomes of kidney transplantation is not fully understood. We investigated a potential effect of mismatching for HLA-DPB1 at allele, eplet, or Terasaki epitope (TerEp) level on the formation of de novo donor-specific antibodies (dnDSA) and also asked whether polymorphisms associated with HLA-DPB1 expression level may influence dnD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 25 publications
3
8
0
Order By: Relevance
“…It is of note that EpMM, which are traditionally associated with antibodyrecognized epitopes, were associated with AR that essentially consisted of TCMR, as all the 19 cases of biopsy proven rejections were diagnosed as TCMR. This finding is consistent with the study by Tang et al, 2 which reported that HLA-DPB1 EpMM or TerEpMM impacted kidney graft survival but were not associated with the development of HLA-DPB1 DSA. On the other hand, the association of HLA-DPB1 expression and EpMM with HLA-DP DSA development was reported in solid organ transplantation, however the study did not report the type of organs included.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…It is of note that EpMM, which are traditionally associated with antibodyrecognized epitopes, were associated with AR that essentially consisted of TCMR, as all the 19 cases of biopsy proven rejections were diagnosed as TCMR. This finding is consistent with the study by Tang et al, 2 which reported that HLA-DPB1 EpMM or TerEpMM impacted kidney graft survival but were not associated with the development of HLA-DPB1 DSA. On the other hand, the association of HLA-DPB1 expression and EpMM with HLA-DP DSA development was reported in solid organ transplantation, however the study did not report the type of organs included.…”
Section: Discussionsupporting
confidence: 93%
“…17 The present study did not detect any association of HLA-DPB1 allelic MM with AR or low 5Y-GF, in line with previous reports of lack of association between HLA-DP antigenic/allelic MM and survival of first kidney grafts. 1,2 All HLA-DPB1 mMM types, as well as higher levels of donor terminal Cr, were more frequent in cases with AR, in univariate analyses. The multivariate analyses were performed including donor terminal Cr and only one of the mMM types in each model, since all the polymorphisms in the HLA-DPB1 gene that determine the mMM are closely correlated.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations